2021
DOI: 10.1007/s11837-020-04496-8
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphorus from Si-Fe Alloy by CaO-Al2O3-SiO2-Na2O Slag Refining

Abstract: A combination of slag and solvent refining methods was used to remove phosphorus from silicon. The CaO-Al 2 O 3-SiO 2-Na 2 O quaternary system was selected as the slag to eliminate phosphorus from Si-20 wt.% Fe alloy at 1300°C. The partition ratio of phosphorus (L P) at various slag compositions was obtained to investigate the effect of basicity (CaO/SiO 2), oxygen potential (SiO 2 /Al 2 O 3) and Na 2 O content of the slag. The maximum value for L P was 1.19 at CaO/SiO 2 of 1.36, SiO 2 /Al 2 O 3 of 1.56 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The optimum composition for maximum removal of B and P from the Si-Fe alloy was determined by the authors and has been reported in previous publications [22,23]. The optimum impurity removal at 1300 • C was achieved at CaO/SiO 2 of 1.5, SiO 2 /Al 2 O 3 of 2, and 10 wt% Na 2 O for the quaternary slag.…”
Section: Slag Preparationmentioning
confidence: 64%
See 1 more Smart Citation
“…The optimum composition for maximum removal of B and P from the Si-Fe alloy was determined by the authors and has been reported in previous publications [22,23]. The optimum impurity removal at 1300 • C was achieved at CaO/SiO 2 of 1.5, SiO 2 /Al 2 O 3 of 2, and 10 wt% Na 2 O for the quaternary slag.…”
Section: Slag Preparationmentioning
confidence: 64%
“…Understanding the thermodynamics and kinetics of B and P distribution between the slag and alloy phases is crucial for process control. A significant number of investigations were carried out on the thermodynamic analysis of Si refining [18,19,[22][23][24][25][26][27][28]. However, kinetic analysis on the mass transfer of B and P between the alloy and slag phases is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of a large amount of Na 2 O-bearing slag during the sodium smelting of VTM, it has a very good effect on the removal of impurities [28][29][30]. If lowtitanium-content molten iron can be obtained by adjusting the process parameters, it will greatly broaden its use and enhance its value.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant efforts of researchers have been focused on the search for new and improving existing technologies for the production and refining of silicon, which make it possible to obtain high-quality silicon that most fully meets the requirements of consumers [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%